Mentalizing in the context of Mentzos’ dilemma–on the use of implicit work in the treatment of non-affective psychosis - Bröcker, Anna-Lena; von Haebler, Dorothea; Lempa, Günter; Montag, Christiane (Frontiers in Psychiatry, 2023)
Current approaches to the treatment of non-affective psychosis include elements of mentalization-based treatment and the potential in enhancing mentalizing capacity in this patient group has been widely emphasized. This article presents the “psychotic identity dilemma”, a concept by Stavros Mentzos, and a therapeutic approach considering this concept as a valuable complementary addition to these treatments. The idea of a dilemma between closeness and distance, which in itself cannot be represented mentally at first, helps to respond to specific needs of patients with psychotic disorders by placing the treatment focus on fundamental interpersonal processes. Following this train of thought, this article attempts to shed light on the importance of the “real relationship” between therapist and patient as well as the exploration of the “here and now”, especially at the beginning of psychotherapeutic treatment. Two treatment modes are suggested, one characterized by the experience of interpersonality within the therapeutic relationship and a second one characterized by the reflection of interpersonal phenomena. These modes are framed by Stavros Mentzos’ concept of an identity dilemma. We describe how mentalizing first needs to be addressed implicitly in a tolerable, exemplary relationship in which closeness and distance are regulated based on the therapist’s countertransference, then explicitly. A series of interventions are described, which allow for moments of shared attention, promote intentionality and contingency and, later in the course of therapy, help to integrate experiences into narratives.